A NARRATIVE REVIEW: PEMANFAATAN TEKNOLOGI DIGITAL OLEH APOTEKER DALAM PENINGKATAN KEPATUHAN PENGOBATAN PENYAKIT KRONIS - Anisya, Kharina (Universitas Pekalongan, 2025)
Background : The increasing prevalence of chronic diseases such as diabetes, hypertension, and cardiovascular disorders poses a major challenge to global health systems. A key determinant of successful chronic disease therapy is patient adherence to medication, which remains low, particularly among populations with limited access to healthcare services. Pharmacists play a crucial role in supporting medication adherence through digital technology–based interventions, such as telepharmacy and mobile health applications. The digitalization of pharmacy services enables improved access, therapy monitoring, and continuous communication between pharmacists and patients. Objective : This study aims to explore the implementation of digital technology by pharmacists in enhancing medication adherence among patients with chronic diseases. Method : A narrative review was conducted through a search of the PubMed, ProQuest, and Google Scholar databases for articles published between 2015 and 2025. Inclusion criteria were applied based on the relevance to pharmacist-led interventions and adherence outcomes among patients with chronic diseases. Ten eligible articles were selected and analyzed qualitatively. Result : The review findings indicate that digital interventions by pharmacists—including telepharmacy, mobile applications, web-based systems, and short message reminders—consistently improve medication adherence and clinical outcomes among patients. Several studies reported reductions in Drug-Related Problems (DRPs), improvements in quality of life, and better control of clinical parameters such as blood pressure and glucose levels. The success of these interventions is influenced by patients’ digital literacy, the support of the healthcare system, and the frequency of communication between pharmacists and patients. Identified barriers include limited internet access, low digital literacy among elderly patients, and insufficient interprofessional collaboration. Conclusion : The utilization of digital technology in pharmaceutical interventions has proven effective in improving medication adherence and clinical outcomes among patients with chronic diseases. The role of pharmacists as digital care facilitators serves as a key factor in achieving these positive results. The integration of telepharmacy and health applications into primary care services holds great potential to expand access and support a more inclusive and sustainable health system. Keywords: telepharmacy, digital technology, medication adherence, chronic disease.